Arabic Language and Islamic Epistemology in Muhammadiyah Education: A Bayani Burhani and ‘Irfani Approach to the SDGs - Ahmadi; Ismail; Septyana Tentiasih; Hanip Hidayatulloh (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to reconceptualize the Arabic language as the epistemological axis of Islamic education within the Muhammadiyah educational system, positioning it as a strategic medium for integrating revelation (wahy), reason (ʿaql), and spiritual intuition (dzauq) in response to contemporary educational challenges and the Sustainable Development Goals (SDGs). Theoretical framework: The theoretical framework is grounded in the triadic epistemology of bayani, burhani, and ‘irfani, as articulated by al-Jābirī and recontextualized in Islamic educational thought, wherein Arabic functions not merely as a linguistic tool but as a unifying epistemic structure. Literature review: The literature review reveals that most existing studies approach Arabic instruction from pedagogical, grammatical, or communicative perspectives, while its epistemological role in shaping Islamic knowledge and ethical reasoning remains underexplored. Recent scholarly debates highlight the urgency of repositioning Arabic as a living epistemology capable of sustaining intellectual depth, and ethical responsibility. Methods: This research adopts a qualitative philosophical approach, drawing on Muhammadiyah institutional documents, curricular guidelines, and classical as well as contemporary Islamic scholarship. Data are analyzed through conceptual triangulation by integrating textual (bayani), rational (burhani), and intuitive (‘irfani) modes of reasoning. Results: The findings demonstrate that Arabic, when framed as an epistemic medium, enables integrative learning, bridges the dichotomy between religious and scientific knowledge, and cultivates ethical consciousness aligned with sustainable educational development. This epistemological integration supports Muhammadiyah’s vision of Islam berkemajuan by promoting inclusive, reflective, and values-based education. Implications: The implications of this study suggest that repositioning Arabic within Islamic education can contribute to sustainable knowledge formation, moral reasoning, and intercultural understanding, reinforcing the ethical foundations of the SDGs. Novelty: The novelty of this research lies in introducing the concept of Arabic as an epistemological ecology, offering a transformative framework that advances Islamic educational renewal beyond linguistic and technical boundaries.